IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM PEMBELAJARAN PENDIDIKAN AL-ISLAM DI SMA MUHAMMADIYAH 2 SIDOARJO - Hazyimara, Karunia; Umar, M. Shabir; Mardiana, Mardiana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research was conducted as an analysis of the gaps that occur in Al-Islam Education. The label of religion that can become a dogma in society about behavior that good and bad activities be so as to encourage people to behave well, in fact no longer works. The increasingly widespread moral degradation is taken seriously by the government with the existence of differentiated learning in the Merdeka Curriculum which can build a pleasant and meaningful learning atmosphere so that the values of Islamic teachings can be conveyed completely. This study used qualitative research with primary data through interviews with Al-Islam Education teachers at SMA Muhammadiyah 2 Sidoarjo. Data processing and analysis techniques gradually through data reduction, data presentation and conclusions. This research shows that the implementation of differentiated learning in Al-Islam Education at SMA Muhammadiyah 2 Sidoarjo is carried out well and systematically through 3 stages, namely planning, learning, implementing learning, and evaluating learning. The planning stage is carried out training related to learning, diagnostic assessment, formulation of learning outcomes, learning objectives, Learning Objectives Flow (ATP), and teaching modules. The implementation stage is a means for teachers, students, and learning resources to interact with the principle of independence so that teachers organize learning based on the needs of students. The last stage is evaluation, both formative carried out during learning and summative contained at the end of learning aimed at assessing and improving the learning that has been carried out.